Negative stimuli may improve visuospatial working memory. (September 2016) - Wilson, Kyle M.; Russell, Paul N.; de Joux, Neil R.; Blakely, Megan J.; Helton, William S.
The impact of negative affect on working memory performance is unclear. Visuospatial and verbal working memory are critical in many settings, but may be impaired during exposure to negative stimuli. In Experiment 1, the impact of task-irrelevant negative picture stimuli on verbal compared to visuospatial working memory performance was investigated. Unexpectedly, visuospatial memory performance was superior for trials containing negative stimuli than trials with neutral stimuli. The impact of negative picture stimuli on visuospatial working memory was further examined in Experiment 2. Performance was again superior for negative stimuli relative to neutral stimuli. While much previous research has reported that negative affect is disruptive of visuospatial working memory, the improved performance found here is consistent with other research particularly where negative or arousing stimuli are thought to increase the pool of available processing resources or effort. Implications for contexts where working memory demands occur alongside distressing stimuli are discussed, as well as future research suggestions.